IMPLEMENTATION OF AN INTERACTIVE E-STUDENT WORKSHEETS INTEGRATED BY STEM ON UNIFORM STRAIGHT MOTION AND NON UNIFORM STRAIGHT MOTION MATERIAL TOWARDS STUDENT CONCEPT UNDERSTANDING (Jurnal Sains dan Matematika, 2023)
This research aims to find out how students understanding of the concept of uniform straight motion and uniform straight motion changes after implementing the STEM integrated interactive E-LKPD. This research was conducted class with the research sample selected using purposive sampling techniques. This research uses a descriptive quantitative method with a one group pretest-posttest design. Research data was collected through pre-test and post-test using test instruments arranged according to indicators of concept understanding. This research was carried out in 4 meetings. The results of the research were that students' understanding of concepts increased after implementing the interactive E-LKPD integrated with STEM GLB and GLBB material. It is known that the average score for students' pre-test scores is 9.25 and the average score for students' post-test scores is 11.94. The results of the Wilcoxon test will produce a value (Asymp. Sig. 2-tailed). If the value of Asymp. Sig. 2-tailed is less than the significance level of 0.05. The conclusion of this research is that STEM integrated interactive E-LKPD can improve students' understanding of learning concepts in the material of uniform straight motion and uniform changing straight motion in class XI MIPA 2 SMAN 2 Sungai Penuh